PENGARUH EKSTRAK JAHE (Zingiber officinale) TERHADAP PERTUMBUHAN MISELIA DAN VIABIL ITAS SPORA JAMUR PERUSAK DODOL - , EKO ADI NUGROHO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dodol is a Intermediate Moisture Food (IMF) which had water activity 0.7 â 0.79. It could be spoilage by fungi during storage especially xerophiles fungi. Ginger (Zingiber officinale) included of spices which had antifungal activity and usually added in food. Water ginger extract could be used as natural preservation agent to replaced chemical preservative in dodol. This research was carried out to study the effect of water ginger extract as natural preservation agent against mycelium growth and spore viability of dodol spoilage fungi. Ginger extract was used in this research was made from fresh gingers which were extracted with steril water ( 1:1 w/v) in blender. The ginger extract was filtrated with cloth , centrifuged (3000 rpm, 10 minute) and filtrared again with double layer Whatman no 1 steril paper. Spoilage fungi was isolated by direct platting method on Czapek Yeast Extract Agar medium with 20 % of sucrose (CY20S). The mycelium growth assay was done by inoculated of one point of spore suspension in the middle of CY20S medium which added by ginger extract and the diameter of colony was measured during incubation time. The spore viability assay was done by inoculated of spore suspension with spread plate method on Czapek Yeast Extract Agar (CYA) medium and the colony was calculated during incubation time. The incubation time was five days at 30oC and the concentration of ginger (Zingiber officinale) extract on medium assay were 0%,2%, 4%, 6%, 8%, and 10%. There were six isolated of spoilage fungi, three isolate belong to Aspergilus genera (J1B-A, J1MA-B, J1B-C ) and three isolate belong to Monascus (J2MA-D, J4MA-E, J4B-F ). The result of mycelium growth assay showed that addition of water ginger extract increased the inhibitor activity of mycelium growth. But, the addition of ginger extract until 10 % could not stop the growth of all isolate fungi. The result of spore viability assay showed that the ginger extract delayed the germination and decreased spore viability of spoilage fungi. Addition of 8 â 10 % of water ginger extract delayed germination of Aspergillus J1B-A for two day and decreased spore viability until 64,68%. Concentration water ginger extract 6 â 10 % also delayed the germination of Monascus J2MA-D for one day and decreased spore viability until 89.47%.